The effects of video content within e-participation platforms on behavioural intention: an analysis of new forms of digital political engagement of young adults in germany on the example of the app “followthevote” - Heinz, Maren (2021)
Purpose - Young citizens in Europe are witnessing a decline in voter turnout, political party membership, and interest in politics. As young people spending a significant amount of time on social media, e-participation tools could use some social media engagement mechanisms to their own advantage. Therefore, this study aims to analyse the effects on the acceptance and use of the E-Participation platform FollowTheVote in Germany. In particular, the effect of video content on behavioral intention is measured. Methodology - A quantitative panel study, over seven days, was conducted with a group of 58 prototype testers. The treatment group was exposed to video content from day three onwards, whereas the control group was exposed to the same written form of content over seven days. The research framework is based on the Technology Acceptance Model which has been extended to fit the context of e-participation platforms. Findings - The results indicate that Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment have a statistically significant positive effect on the Behavioural Intention of the eparticipation platform FollowTheVote. However, the implementation of video content has shown no statistically significant effect on the acceptance and use of the platform. Research Limitations - The research is limited by the relatively small sample size. Research Implications – This study contributes to the information systems literature by expanding the understanding of the relationship between content forms and the acceptance and use of information technology in the context of political information systems. Practical Implications – The practical contribution of this research is the validation of the market potential of FollowTheVote, a project of the NGO Political Innovation Association (PIA) e.V. and to political innovation in this sector. Originality: To my knowledge, no similar analysis on the effects of video content on the behavioral intention of E-Participation tools exists.